The Effect of Service Quality and Facilities on Customer Satisfaction at Panjerejo Pharmacy - Hasibuan, Delila Amelia; Anasrulloh, Muhammad (JURNAL MANAJEMEN MUTU PENDIDIKAN, 2024)
Current economic developments have led to increasingly tight competition, especially in sectors such as pharmacies. One of the pharmacies in the Tulungagung area is the Panjerejo pharmacy located in the Ngunut sub-district. This study aims to determine the effect of service quality and facilities on customer satisfaction at the Panjerejo Pharmacy. This study is a type of quantitative research. The population used is all customers of the Panjerejo Pharmacy. The sample used was 100 people obtained from calculations using the Lemeshow formula. Data collection techniques by distributing questionnaires or surveys to respondents. The Effect of Service Quality and Facilities at the Panjerejo Pharmacy on Customer Satisfaction. Simultaneously shows that Service Quality and Facilities have a significant effect on Customer Satisfaction with the results of F count (82.594) > F table (3.089) and a significance value of 0.000 <0.05. The customized R2 value is 0.622, which means that Service Quality and Facilities affect Customer Satisfaction by 62.2% and the remaining 62.2% of Customer Satisfaction is influenced by the Service Quality variable and 37.8% of Customer Satisfaction is influenced by other variables not studied. . Keywords: Service Quality; Facilities; Visitor Satisfaction.DOI: 10.23960/jmmp.v12.i2.2024.30687